English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-02-28 02:26:18 · 8 answers · asked by Anonymous in Science & Mathematics Mathematics

8 answers

No, the apparatus is shown as:

1. 3y=x+16
2. 3y-x=x-(x)+16 [Subtract x from each side or subtractive property of equality]
3. 3y-x=16
4. -x+3y=16
(Opt.) You seem to have multiplied the whole equation by 4. You have a multiplication error in step 5
5. 4*(-x+3y)=16*(4) [Multiplicative property of equality]
6. -4x +12y= 64 [16 multiplied by 4 isn't 68!]

There you have it, have fun!

(Everyone who has anwered above has some flaw in it!)

2007-02-28 02:37:16 · answer #1 · answered by ĦΛЏĢħŦŞŧμρђ 2 · 0 0

No.
3y = x + 16
-x + 3y = 16
-4x + 12y = 64, not 68

2007-02-28 02:30:49 · answer #2 · answered by Phred 3 · 0 0

You have got the question wrong, it should have been:
Is 3y=x+16 the same as saying -4x+12y=64?
In this case, YES when both the equations are simplified.
3y=x+16
=>3y-x=16

And
-4x+12y=64
=>12y-4x=64
=>3y-x=16 (Dividing LHS and RHS each by 4)

2007-02-28 02:33:43 · answer #3 · answered by You-Know-Who 2 · 0 1

No. Your 68 should be 64. You essentially multiplied
the equation by 4.

2007-02-28 02:34:35 · answer #4 · answered by steiner1745 7 · 0 0

No, because 16 * 4 = 64.

2007-02-28 02:30:03 · answer #5 · answered by Amit Y 5 · 1 0

no its not
you can take 2 into it all to be -2x+6y=34
take two into all again
that equals 3y=x=17

2007-02-28 02:34:26 · answer #6 · answered by christine m 1 · 0 0

no: for the above mentioned reasons

2007-02-28 02:35:49 · answer #7 · answered by Maths Rocks 4 · 0 1

no

2007-02-28 02:32:28 · answer #8 · answered by Rick 5 · 0 1

fedest.com, questions and answers